Enhancing Historical Understanding Through the Team Games Tournament “Clash of Champions”: A Deep Learning Approach - Nuhiyah Nuhiyah; Rizky Khairina; Ratih Lutfita Ningtyas; Nashar Nashar (Universitas Hamzanwadi, 2026)
The history subject plays a vital role in teaching valuable lessons from the past that can be applied to the present world, regardless of geographical or cultural barriers. Traditional teaching methods, based on facts and uninspiring textbooks, contribute to student disinterest and superficial understanding of history. The implementation of deep learning approach can be realized through the Team Games Tournament learning model, which uses team games to enhance student engagement, understanding, and skills, as well as support meaningful and enjoyable deep learning. This study aims to examine the effectiveness of the Team Games Tournament “Clash of Champions” in improving students' history comprehension through a deep learning approach. The research uses a quantitative method with a Quasi-Experimental Nonequivalent Group Design. The subjects comprise one control class and one experimental class, with a total of 65 students. The results indicate that implementing the Team Games Tournament “Gameshow Clash of Champions” significantly improves students' understanding of history. Through a deep learning approach, this innovation provides a meaningful, enjoyable, and conscious learning experience that aligns with 21st-century learning needs.